NAVIGATING THE CHALLENGES: A SWOT ANALYSIS OF IMPLEMENTING SMOKING TOBACCO POLICIES FOR MINORS IN KARACHI, PAKISTAN - Jonathan Johnson; Wafa Aftab; Romaina Iqbal; Narjis Rizvi; Rubeka Mansha; Fazila Thawer; Zeeshan Aslam (Policy Research Journal, 2025)
The rising prevalence of tobacco use among minors in Karachi poses a significant public health threat. Despite existing regulations, enforcement remains weak, leaving young people vulnerable to smoking initiation. This research aims to evaluate the strengths, weaknesses, opportunities, and threats (SWOT) in implementing smoking tobacco policies targeting minors in Karachi. Through qualitative analysis and expert interviews, the study identifies key areas where policy enforcement can improve and potential barriers. The findings reveal gaps in policy application, opportunities for community engagement, and challenges such as social acceptance of tobacco use. Recommendations include stricter regulations, awareness campaigns, and collaboration with local authorities. Implementing these policies effectively is crucial for safeguarding the health of Karachi's youth and aligning with broader public health goals.